Efficient spin control in high-quality-factor planar microcavities - Quinteiro, Guillermo Federico (2012)
A semiconductor microcavity embedding donor impurities and excited by a laser field is modeled. By including general decay and dephasing processes, in particular, cavity photon leakage, detailed simulations show that control over the spin dynamics is significantly enhanced in high-quality-factor cavities, in which case picosecond laser pulses may produce spin flip with high-fidelity final states. © 2012 American Physical Society.